Ways to optimize the teaching of the Russian language and literature in the national school (The Peerian Journal, 2022)
The article discusses the features of the intellectual development of the student, his skills and abilities, techniques for enhancing cognitive activity in Russian language lessons. The questions of optimization of the lesson are studied as a purposeful approach of the teacher to the construction of the educational process.